Le Corbusier: Chandigarh and the modern city : insights into the iconic city sixty years later - Khan, Hasan-Uddin ed.; Beinart, Julian ed.; Correa, Charles ed. (Mapin Publishing, Ahmedabad, 2009)
The book revisits the Chandigarh and examines its built and social form in terms of today's perspectives, reviewing the changes in the city and to the lives of its inhabitants and its architecture.
Keywords: AR